No association between RORA polymorphisms and PTSD in two independent samples - Guffanti, G; Ashley-Koch, A E; Roberts, A L; Garrett, M E; Solovieff, N; Ratanatharathorn, A; De Vivo, I; Dennis, M; Ranu, H; Smoller, J W; Liu, Y; Purcell, S M; et al. (Molecular psychiatry, 2014)
A C A T